Seismic response analysis of a geogrid reinforced wall constructed with recycled Construction and Demolition Waste - Castorina Silva Vieira (2015)
Over the last years the environmental sustainability has been demanding a progressive increase in the waste valorisation in construction. The valorisation of Construction and Demolition Wastes (C&DW) reduces the use of natural resources (non-renewable) and, simultaneously, avoids congesting landfills with inert wastes coming from buildings and other infrastructures. Although some studies have been carried out on the use of recycled C&DW in construction industry, their valorisation as fill material in geosynthetic reinforced structures is almost an unexplored field. A research project aiming to contribute to the sustainable application of recycled C&DW as backfill material in geosynthetic reinforced structures, is being developed at University of Porto, Portugal. Preliminary results of this research are presented in this paper. In this work the two-dimensional finite difference program Fast Lagrangian Analysis of Continua (FLAC) was used to model the behaviour of a geogrid reinforced wall, constructed in Brazil, with recycled C&DW. The wall is 3.6m high and was constructed at an inclination of 1:4.3 (wall batter of 13° from vertical). The backfill was reinforced with six layers of geogrid placed at 0.6 m of vertical spacing and 2.52 m long. The seismic response of a similar wall, hypothetically constructed with recycled C&DW coming from a Portuguese recycling plant, is also evaluated. An earthquake ground motions artificially generated for the greatest seismicity area of Portugal was considered as seismic input. Two constitutive models were used to model the backfill C&DW material: the Mohr-Coulomb model and a Strain-Softening model. Permanent displacements of the wall face, settlements and reinforcement tensile forces are analysed and discussed. The numerical simulations have shown that the possible decrease of the backfill shear strength during cyclic loading is an important issue to be studied more closely. Notwithstanding it was concluded that a well compacted and drained recycled C&DW can be used as fill material in geosynthetic reinforced structures.